A Rare Case Report of Gastric Adenocarcinoma with Pneumoperitoneum after Jejunostomy Feeding - Sukmagautama, Coana; Asaduddin, Aiman Hilmi; Syahrizal, Maulana Firdaus; Khasan, Arif Nur; Putri, Desy Puspa (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Gastric cancer is the third highest cancer mortality globally. This malignancy can result in emergency complications such as gastric perforation which results in pneumoperitoneum. Currently, there are not many case reports which describe pneumoperitoneum in gastric cancer. In this report, we describe a gastric adenocarcinoma with pneumoperitoneum following jejunostomy feeding. Case Presentation: A 54 years old male presented with abdominal pain, black-colored feces, and body weight decrease as much as 22 kg within a month. The physical examination revealed anemic conjunctiva, distended abdomen with abdominal pain, and pale skin. On the lab examination, the hemoglobin level was 9.9 mg/dL. The peripheral blood smear showed signs of iron deficiency anemia caused by chronic process. An endoscopic examination and biopsy showed a gastric mass with well-moderately differentiated gastric adenocarcinoma. The three positions abdominal x-ray incidentally found that the patient had pneumoperitoneum. Results: Patient was diagnosed with Adenocarcinoma Gaster based on a gastric mass biopsy with hematoxylin-eosin staining. Then, the patient was treated with jejunostomy feeding. Thoracic and 3-position abdominal X-ray examinations revealed incidental findings of pneumoperitoneum and small bowel obstruction. Conclusion: Jejunostomy feeding in gastric cancer patient may result in pneumoperitoneum as a complication. Gastric adenocarcinoma followed by iron deficiency anemia from chronic process post jejunostomy feeding was found with pneumoperitoneum complication.